2019
DOI: 10.1158/0008-5472.can-19-1982
|View full text |Cite
|
Sign up to set email alerts
|

MFF Regulation of Mitochondrial Cell Death Is a Therapeutic Target in Cancer

Abstract: The regulators of mitochondrial cell death in cancer have remained elusive, hampering the development of new therapies. Here, we showed that protein isoforms of mitochondrial fission factor (MFF1 and MFF2), a molecule that controls mitochondrial size and shape, that is, mitochondrial dynamics, were overexpressed in patients with non-small cell lung cancer and formed homo-and heterodimeric complexes with the voltage-dependent anion channel-1 (VDAC1), a key regulator of mitochondrial outer membrane permeability.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…These data are in accordance with previous studies showing that MFF-dependent mitochondrial fission activates signaling pathways involved in the inhibition of cell viability and the activation of the apoptotic response (44). In particular, MFF and other mediators involved in mitochondrial fragmentation such as DRP1 play an integral role in cancer cell death in response to diverse stimuli, including several anticancer drugs (45,46). At least some of these effects could be attributed to the generation of mitochondrial ROS, which would thereafter trigger apoptotic cell death (47).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data are in accordance with previous studies showing that MFF-dependent mitochondrial fission activates signaling pathways involved in the inhibition of cell viability and the activation of the apoptotic response (44). In particular, MFF and other mediators involved in mitochondrial fragmentation such as DRP1 play an integral role in cancer cell death in response to diverse stimuli, including several anticancer drugs (45,46). At least some of these effects could be attributed to the generation of mitochondrial ROS, which would thereafter trigger apoptotic cell death (47).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the pharmacological manipulation of mitochondrial fission may serve as an actionable tool to eradicate cancer cells, with tumor initiating capabilities. Accordingly, it has been recently shown that an MFF peptidomimetic strategy elicits anti-cancer activity in patient-derived xenografts, primary breast and lung adenocarcinoma 3D organoids, as well as glioblastoma neurospheres (45).…”
Section: Discussionmentioning
confidence: 99%
“…If this can be generalized to most PCa cases, it would suggest that targeting the TLK1> Nek1> VDAC1 axis could greatly improve the response to appropriate DNA damaging agents. Interestingly, while this paper was undergoing review, an important paper was published, which showed the Mitochondrial Fission Factors (MFF1 and MFF2) formed homo-and heterodimeric complexes with VDAC1 [25]. A cell permeable MFF Ser223-Leu243 D-enantiomeric peptidomimetic disrupted the MFF-VDAC1 complex and acutely depolarized mitochondria triggering apoptosis in several tumors types and in xerografts, but had no effect on normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…A cell permeable MFF Ser223-Leu243 D-enantiomeric peptidomimetic disrupted the MFF-VDAC1 complex and acutely depolarized mitochondria triggering apoptosis in several tumors types and in xerografts, but had no effect on normal cells. Among the cell lines they investigated, they included several PCa lines: LNCaP, C4-2, C4-2B, PC3, and DU145 [25]. Therefore, there is already some indirect evidence that targeting VDAC1 activity, through its phosphorylation by activated Nek1, via inhibition of TLK1 activity could be a very useful means to enhancing PCa cells killing with focused XRT or doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Mff, a key molecule that determines mitochondrial size and shape and the regulation of mitochondrial cell death, is a novel therapeutic target in cancer. 29,30 LATS2 facilitates the apoptosis of non-small cell lung cancer by regulating Mff-induced mitochondrial fission. 31 Furthermore, Mff-induced mitochondrial fission was attributed to decreased colorectal cancer cell viability.…”
Section: Discussionmentioning
confidence: 99%